Inattentive and hyperactive behaviors and driving offenses in adolescence - Nada-Raja, S; Langley, J D; McGee, R; Williams, S M; Begg, D J; Reeder, A I (Journal of the American Academy of Child and Adolescent Psychiatry, 1997)
The associations between symptoms of attention-deficit hyperactivity disorder (ADHD), conduct disorder, anxiety, or depression and no disorder in relation to driving offenses were examined in 916 adolescents. Self-report and parent report were used to assess a birth cohort of New Zealand adolescents' mental health status at age 15 years. Adolescents who scored 1.5 SD above the mean on the DSM-III total ADHD symptom scale were identified as reporting significant ADHD symptomatology. Self-report data and official traffic conviction records were used to identify adolescents who had committed driving offenses between ages 15 and 18 years. ADHD symptomatology and conduct disorder were strongly associated with driving offenses. ADHD symptomatology in females was significantly associated with driving offenses and more traffic crashes compared with other disorder or no disorder. Adolescents with a history of ADHD and conduct problems are significantly more likely than their peers to commit traffic offenses. Research in ADHD and risky driving should include female adolescents, as those with attentional difficulties are at a high risk for being involved in traffic crashes than females who do not experience attentional difficulties.